Bio-inspired lotus root-like 3D multichannel carbon hosts for stable lithium metal anodes. (1st December 2020) - Yu, Lintao; Su, Qingmei; Li, Boyu; Liu, Wuyou; Zhang, Miao; Ding, Shukai; Du, Gaohui; Xu, Bingshe
Highlights: The bio-inspired lotus root-like MCNFs are fabricated by electrospinning strategy. The MCNF is used as a host for the Li metal anode by a thermal infusion strategy. The 3D MCNF provides enough space for volume expansion of Li metal during cycling. When coupled with a LiFePO4 cathode, the MCNF/Li anode shows excellent performance. The MCNF/Li anode has the potential to promote the practical application of LMBs. Abstract: Lithium metal batteries (LMBs) are generally regarded as one of the alternatives for high energy density devices. However, the commercial application of LMBs is seriously restricted by volume changes and dendrite behavior of lithium metal, which cause low efficiency and poor safety. In the present study, and inspired by the structure of the lotus root (which has many interior parallel channels that significantly enlarges the contact area), we have designed lotus root-like 3D multichannel carbon fibers (MCNFs) that are decorated with lithiophilic Ag nanoparticles (Ag NPs). These adhered lithiophilic Ag nanoparticles will facilitate molten Li infusion into the carbon channels, forming stable lithium metal anodes. The ion concentration gradient near the surface Ag protrusions will become reduced, thereby inducing homogeneous nucleation and deposition of Li. The produced multi-channels will provide enough space for volume expansion of Li metal during cycling. As a result, when coupled with a LiFePO4 (LFP) cathode, the MCNF/Ag-Li composite anode maintained 94.7% of its capacity, and 99.1% of the Coulombic efficiency after 600 cycles at 1 C. Moreover, the MCNF/Ag-Li|Li symmetrical cell could be cycled for more than 600 h, with a low hysteresis of 20 mV (at 1 mA cm −1 ), and with the capacity of 1 mAh cm −1 during the whole cycle (without any short-circuit). These results suggest that anodes, made of a lotus root-like 3D multichannel lithium metal composite material, will have the potential to promote the practical applications of lithium metal batteries. Graphical abstract: Inspired by the unique structure of the lotus root, we have, by using a thermal infusion strategy, successfully exploited a lotus root-like 3D MCNF as a stable host for the Li metal anode. The porous carbon fibers have the capacity to load a considerably amount of lithium and can also accommodate volume expansion (despite high specific surface area and large pore volume).This type of material will thereby offer an excellent balance between gravimetric and high energy densities. The carbon multi-channels are to be considered as "nanocages" for the Li metal, ensuring that Li will not be in direct contact with the electrolyte. When coupled with a LiFePO4 cathode, the MCNF/Ag-Li composite anode maintained 94.7% of its capacity, and 99.1% of the Coulombic efficiency after 600 cycles at 1C. Image, graphical abstract